2015
DOI: 10.3389/fpsyt.2015.00098
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind and Context Processing in Schizophrenia: The Role of Social Knowledge

Abstract: The present study sought to determine whether social knowledge such as speaker occupation stereotypes may impact theory of mind (ToM) ability in patients with schizophrenia (SZ). Thirty individuals with SZ and 30 matched healthy control (HC) participants were tested individually on their ToM ability using a paradigm showing that stereotypes such as speaker occupation influences the extent to which speaker ironic intent is understood. ToM ability was assessed with open questions on the speaker ironic intent, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 53 publications
3
13
1
Order By: Relevance
“…In sum, patients with schizophrenia and healthy controls displayed very similar perceptions about the relative typicality of the presented traits. The present findings are strongly in line with those reported by Champagne-Lavau and Charest [15] , who found that patients with schizophrenia and healthy control respondents were equally sensitive to social stereotypes in the domain of professional occupations. Overall, this is consistent with the idea that individuals with schizophrenia have a relatively intact knowledge about socially shared stereotypes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In sum, patients with schizophrenia and healthy controls displayed very similar perceptions about the relative typicality of the presented traits. The present findings are strongly in line with those reported by Champagne-Lavau and Charest [15] , who found that patients with schizophrenia and healthy control respondents were equally sensitive to social stereotypes in the domain of professional occupations. Overall, this is consistent with the idea that individuals with schizophrenia have a relatively intact knowledge about socially shared stereotypes.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, according to prevalent models of social perception [11,23] the early activation of stereotypes represents the basic process that sets the background for all the subsequent stages of impression formation and social interaction. The present and previous findings [15] suggest that individuals with schizophrenia hold the same stereotypical knowledge and expectations as healthy individuals, and likely rely on them in their daily life marked by multiple interactions with other people belonging to a variety of different social groups. A notable limitation of the present studies is that participants were asked to provide rather abstract judgments about the estimated prevalence of stereotypical and counterstereotypical traits in the tar-get groups.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In daily communication, there is a gap between utterance meaning and sentence meaning, and pragmatics helps to construct utterance meaning (Giora, 1995(Giora, , 1997Grice, 1975Grice, , 1991. Many pragmatists and psycholinguists believe that theory of mind (ToM) can help listener to fill in the gap between the two meanings, and it is believed that pragmatic ability is in close relationship to ToM (Champagne-Lavau & Charest, 2015;Champagne-Lavau, Charest, Anselmo, Rodriguez, & Blouin, 2012;Spotorno, Koun, Prado, Van Der Henst, & Noveck, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This allows a wide variety of mental states different from one's own to be understood (Couture et al., ). Patients with schizophrenia are sensitive to social stereotypes (Champagne‐Lavau et al., ), but their ability to mentalize and attribute beliefs remain markedly impaired (Bozikas et al., ).…”
Section: Introductionmentioning
confidence: 99%